Increased oral sodium chloride intake in humans amplifies selectively postprandial GLP‐1 but not GIP, CCK, and gastrin in plasma. Issue 15 (7th August 2020) - Asmar, Ali; Cramon, Per K.; Asmar, Meena; Simonsen, Lene; Sorensen, Charlotte M.; Madsbad, Sten; Moro, Cedric; Hartmann, Bolette; Rehfeld, Jens F.; Holst, Jens J.; Hovind, Peter; Jensen, Boye L.; et al.
Abstract: Human studies have demonstrated that physiologically relevant changes in circulating glucagon‐like peptide‐1 (GLP‐1) elicit a rapid increase in renal sodium excretion when combined with expansion of the extracellular fluid volume. Other studies support the involvement of various gastrointestinal hormones, e.g., gastrin and cholecystokinin (CCK) in a gut‐kidney axis, responsible for a rapid‐acting feed‐forward natriuretic mechanism. This study was designed to investigate the hypothesis that the postprandial GLP‐1 plasma concentration is sensitive to the sodium content in the meal. Under fixed sodium intake for 4 days prior to each experimental day, 10 lean healthy male participants were examined twice in random order after a 12‐hr fasting period. Arterial blood samples were collected at 10–20‐min intervals for 140 min after 75 grams of oral glucose + 6 grams of oral sodium chloride (NaCl) load versus 75 grams of glucose alone. Twenty‐four‐hour baseline urinary sodium excretions were similar between study days. Arterial GLP‐1 levels increased during both oral glucose loads and were significantly higher at the 40–80 min period during glucose + NaCl compared to glucose alone. The postprandial arterial responses of CCK, gastrin, and glucose‐dependent insulinotropic polypeptide as well as glucose, insulin, and C‐peptide did not differ between the two study days. Arterial renin, aldosterone, and natriuretic peptides levels did not change within subjects or between study days. Angiotensin II levels were significantly lower at the time GLP‐1 was higher (60–80 min) during glucose + NaCl. Sodium intake in addition to a glucose load selectively amplifies the postprandial GLP‐1 plasma concentration. Thus, GLP‐1 may be part of an acute feed‐forward mechanism for natriuresis. Abstract : This study demonstrates that postprandial glucose‐driven glucagon‐like peptide‐1 (GLP‐1) secretion is sensitive to dietary sodium chloride intake and that this is associated with significantly lower angiotensin II (ANG II) but not aldosterone concentrations. In perspective, this feed‐forward Na + ‐driven GLP‐1/ANGII response could have an impact on renal Na + ‐handling.